Festschrift für Volker Krey zum 70. Geburtstag am 9. Juli 2010 - Amelung, Knut; Günther, Hans-Ludwig; Kühne, Hans-Heiner (Kohlhammer, 2010)
$qtext/html$uhttp://deposit.d-nb.de/cgi-bin/dokserv?id=3478594&prov=M&dok_var=1&dok_ext=htm$3Inhaltstext